Observer Variability in Head Circumference Measurement Using Routine Versus Non-Stretchable Tapes in Children - Thakkar, Pareshkumar Amrutlal; Yagnik, Kinjal; Parmar, Niyati T; Das, Rashmi Ranjan; Thakkar, Ukti P (Journal of Nepal Paediatric Society, 2018)
Introduction: Observer variability is known in taking head circumference. Stretchable tapes do not provide accurate results after being used repeatedly. The aim of this study was to compare the intra-observer and inter-observer variability in measuring head circumference (HC) or occipito-frontal circumference (OFC) by using routine stretchable and non-stretchable tapes. Material and Methods: In this crosss-ectional study, all stable children in the age group of 1 month to 5 years attending the pediatric department of a tertiary care teaching hospital over six months period were included. The main outcome measures were: intra-observer & inter-observer variability in HC measurements by routinely used stretchable and non-stretchable tapes, and accuracy of readings of old stretchable tapes. Results: A total of 301 children were included. There was good correlation in the measurements taken by two observers (inter-observer), and three different readings of the same observer (intra-observer), correlation coefficient being > 0.99. With stretchable tape, 26% subjects had both intra-observer and inter-observer variability of ≥ 0.5 cm, which was 9.9% and 15.9% with the use of non-stretchable tape, respectively. Non-stretchable tape compared to stretchable tape had significantly less intra-observer (p < 0.001) and inter-observer variability (p=0.038). Conclusions: Observer variability was significantly less with the use of non-stretchable tapes compared to routinely used stretchable tapes. Old stretchable tapes used repeatedly over certain periods were not able to provide accurate readings.